969 Smoking and pulmonary alterations in retired bauxite mining workers: a retrospective study. (24th April 2018) - Ferreira, LR; Priester, LFT; Ferreira, VL; Galhardi, CM; Ferreira, LCR; Bianchi, RCG
Abstract : Introduction: Retired bauxite mining workers have been at risk for developing lung diseases due to their long-term exposure to inhalation hazards. Smoking is known to decrease pulmonary function and cause lung disease. Smoking cessation may prevent these changes. This study aimed to evaluate whether smoking is associated with pulmonary changes in retired bauxite mining workers. Methods: A cross-sectional study involving the database information of 140 retired bauxite mining workers from Brazil evaluated at the Worker's Health Reference Centre and Social Security National Institute, from July 2015 until June 2016. The workers were divided in 3 groups: smokers (n=47), non-smokers (n=47), and ex-smokers (n=46). The data included: gender, age, spirometric results (normal; altered results including mild, moderate or severe changes), and presence of pulmonary parenchymal alterations in chest x-rays. It was applied the Chi-Squared test with p<0, 05. Results: All workers were male with mean age of 62 years-old. In the smokers group, 83% spirometry tests were altered (53% mild, 19% moderate and 11% with severe changes). In this group, 64% had altered chest x-rays. In the non-smokers group, 19% spirometry tests were altered (13% mild and 6% moderate changes). In this group, 13% had altered chest x-rays. In the ex-smokers group, 35% spirometry tests were altered (11% mild, 9% moderate and 15% severe changes). In this group, 30% had altered x-rays. All results were statistically significant, except for the mild changes in the non and ex-smokers groups. Discussion: These results demonstrated differences between the smokers and non-smokers groups in regard to spirometric and radiographic alterations. The ex-smokers group had improved results compared to the smokers group in regard to altered spirometric and chest x-rays findings. These data may contribute with strategies to enhance smoking cessation programs within the bauxite mining industry in order to prevent pulmonary changes in mining workers.